Digital Modulation: Saravanan Vijayakumaran Sarva@ee - Iitb.ac - in
Digital Modulation: Saravanan Vijayakumaran Sarva@ee - Iitb.ac - in
Digital Modulation: Saravanan Vijayakumaran Sarva@ee - Iitb.ac - in
Saravanan Vijayakumaran
sarva@ee.iitb.ac.in
August 8, 2012
1 / 45
Digital Modulation
Definition
The process of mapping a bit sequence to signals for
transmission over a channel.
p(t) −p(t)
t t
−A
2 / 45
Classification of Modulation Schemes
• Memoryless
• Divide bit sequence into k -bit blocks
• Map each block to a signal sm (t), 1 ≤ m ≤ 2k
• Mapping depends only on current k -bit block
• Having Memory
• Mapping depends on current k -bit block and L − 1 previous
blocks
• L is called the constraint length
• Linear
• Modulated signal has the form
X
u(t) = bn g(t − nT )
n
3 / 45
Signal Space Representation
Signal Space Representation of Waveforms
• Given M finite energy waveforms, construct an
orthonormal basis
N
X
si (t) = si,n φn (t), i = 1, . . . , M
n=1
T
• si (t) is represented by the vector si = si,1 · · · si,N
• The set {si : 1 ≤ i ≤ M} is called the signal space
representation or constellation
5 / 45
Constellation Point to Waveform
φ1 (t)
si,1 ×
φ2 (t)
si,2 ×
.. ..
. .
+ si (t)
φN−1 (t)
si,N−1 ×
φN (t)
si,N ×
6 / 45
Waveform to Constellation Point
φ∗1 (t)
si,1
R
×
φ∗2 (t)
si,2
R
×
.. .. ..
. . .
si (t)
φ∗N−1 (t)
si,N−1
R
×
φ∗N (t)
si,N
R
×
7 / 45
Gram-Schmidt Orthogonalization Procedure
• Algorithm for calculating orthonormal basis
• Given s1 (t), . . . , sM (t) the k th basis function is
γk (t)
φk (t) = √
Ek
where
Z ∞
Ek = |γk (t)|2 dt
−∞
−1
kX
γk (t) = sk (t) − ck ,i φi (t)
i=1
ck ,i = hsk (t), φi (t)i, i = 1, 2, . . . , k − 1
8 / 45
Gram-Schmidt Procedure Example
s1 (t) s3 (t)
1 1
3 t
2 t
-1
s2 (t) s4 (t)
1 1
2 t 3 t
-1 -1
9 / 45
Gram-Schmidt Procedure Example
φ1 (t) φ3 (t)
1
√1
2
2 3 t
2 t
-1
φ2 (t)
√ T
s1 = 2 0 0
√ T
√1
2 s2 = 0 2 0
2 t √ T
s3 = 2 0 1
− √1
2
√ T
s4 = − 2 0 1
10 / 45
Properties of Signal Space Representation
• Energy
Z ∞ N
X
Em = |sm (t)|2 dt = |sm,n |2 = ksm k2
−∞ n=1
• Inner product
hsi (t), sj (t)i = hsi , sj i
11 / 45
Modulation Schemes
Pulse Amplitude Modulation
• Signal Waveforms
Am = 2m − 1 − M, 1≤m≤M
Example (M=4) A1 = − 3, A2 = − 1, A3 = + 1, A4 = + 3
• Baseband PAM: p(t) is a baseband signal
• Passband PAM: p(t) = g(t) cos 2πfc t where g(t) is
baseband
13 / 45
Constellation for PAM
M=2
0 1
M=4
00 01 11 10
14 / 45
Phase Modulation
• Complex Envelope of Signals
π(2m−1)
sm (t) = p(t)e j M , 1≤m≤M
15 / 45
Constellation for PSK
QPSK, M = 4
01 11
00 10
Octal PSK, M = 8
011 001
010 000
110 100
111 101
16 / 45
Quadrature Amplitude Modulation
• Complex Envelope of Signals
17 / 45
Constellation for QAM
16-QAM
18 / 45
Power Spectral Density of Digitally Modulated
Signals
PSD Definition for Digitally Modulated Signals
• Consider a real binary PAM signal
∞
X
u(t) = bn g(t − nT )
n=−∞
20 / 45
Cyclostationary Random Process
Definition (Cyclostationary RP)
A random process X (t) is cyclostationary with respect to time
interval T if it is statistically indistinguishable from X (t − kT ) for
any integer k .
21 / 45
Stationarizing a Cyclostationary Random Process
Theorem
Let S(t) be a cyclostationary random process with respect to
the time interval T . Suppose D ∼ U[0, T ] and independent of
S(t). Then S(t − D) is a stationary random process.
Proof Sketch
Let V (t) = S(t − D). We prove that V (t1 ) ∼ V (t1 + τ ).
Z T
1
P [V (t1 + τ ) = v ] = P [S(t1 + τ − x) = v ] dx
T 0
Z T −τ
1
= P [S(t1 − y ) = v ] dy
T −τ
Z T
1
= P [S(t1 − y ) = v ] dy
T 0
= P [V (t1 ) = v ]
22 / 45
Stationarizing a Cyclostationary Random Process
Proof Sketch (Contd)
We prove that V (t1 ), V (t2 ) ∼ V (t1 + τ ), V (t2 + τ ).
P [V (t1 + τ ) = v1 , V (t2 + τ ) = v2 ]
1 T
Z
= P [S(t1 + τ − x) = v1 , S(t2 + τ − x) = v2 ] dx
T 0
1 T −τ
Z
= P [S(t1 − y ) = v1 , S(t2 − y ) = v2 ] dy
T −τ
1 T
Z
= P [S(t1 − y ) = v1 , S(t2 − y ) = v2 ] dy
T 0
= P [V (t1 ) = v1 , V (t2 ) = v2 ]
23 / 45
Stationarizing a Wide Sense Cyclostationary RP
Theorem
Let S(t) be a wide sense cyclostationary RP with respect to the
time interval T . Suppose D ∼ U[0, T ] and independent of S(t).
Then S(t − D) is a wide sense stationary RP.
Proof Sketch
Let V (t) = S(t − D). We prove that mV (t) is a constant function.
Z T Z T
1 1
E [E [S(t − D)|D]] = mS (t − x) dx = mS (y ) dy
T 0 T 0
24 / 45
Stationarizing a Wide Sense Cyclostationary RP
Proof Sketch (Contd)
We prove that RV (t1 , t2 ) is a function of t1 − t2 = kT +
25 / 45
Power Spectral Density of a Realization
Time windowed realizations have finite energy
PSD of a realization
|STo (f )|2
S̄x (f ) = lim
To →∞ To
To
|STo (f )|2
Z
1 2
−
*
−
) xTo (u)xT∗o (u − τ ) du = R̂s (τ )
To To − T2o
26 / 45
Power Spectral Density of a Cyclostationary Process
S(t)S ∗ (t − τ ) ∼ S(t + T )S ∗ (t + T − τ ) for cyclostationary S(t)
Z To
1 2
R̂s (τ ) = s(t)s∗ (t − τ ) dt
To − T2o
Z KT
1 2
= s(t)s∗ (t − τ ) dt for To = KT
KT − KT
2
K
Z T 2
1 1 X
= s(t + kT )s∗ (t + kT − τ ) dt
T 0 K K
k =− 2
Z T
1
→ E [S(t)S ∗ (t − τ )] dt
T 0
Z T
1
= RS (t, t − τ ) dt = RV (τ )
T 0
or
28 / 45
Power Spectral Density of Linearly Modulated
Signals
PSD of a Linearly Modulated Signal
• Consider
∞
X
u(t) = bn p(t − nT )
n=−∞
|P(f )|2
Su (f ) = Sb e j2πfT
T
30 / 45
PSD of a Linearly Modulated Signal
Ru (τ )
Z T
1
= Ru (t + τ, t) dt
T 0
Z T ∞ ∞
1 X X
∗
= E [bn bm p(t − nT + τ )p∗ (t − mT )] dt
T 0 n=−∞ m=−∞
∞ ∞ Z −(m−1)T
1 X X
∗
= E [bm+k bm p(u − kT + τ )p∗ (u)] du
T
k =−∞ m=−∞ −mT
∞ Z ∞
1 X
∗
= E [bm+k bm p(u − kT + τ )p∗ (u)] du
T
k =−∞ −∞
∞ Z ∞
1 X
= Rb [k ] p(u − kT + τ )p∗ (u) du
T −∞
k =−∞
31 / 45
PSD of a Linearly Modulated Signal
∞ Z ∞
1 X
Ru (τ ) = Rb [k ] p(u − kT + τ )p∗ (u) du
T −∞
k =−∞
Z ∞
p(u + τ )p∗ (u) du *
−
− |P(f )|
)
2
−∞
Z ∞
p(u − kT + τ )p∗ (u) du *
− 2 −j2πfkT
− |P(f )| e
)
−∞
∞
|P(f )|2 X
Su (f ) = F [Ru (τ )] = Rb [k ]e −j2πfkT
T
k =−∞
|P(f )|2
= Sb e j2πfT
T
P∞ −k .
where Sb (z) = k =−∞ Rb [k ]z
32 / 45
Power Spectral Density of Line Codes
Line Codes
0 1 1 0 1 1 1 0 1 0 1
Unipolar NRZ
Polar NRZ
Bipolar NRZ
Manchester
34 / 45
Unipolar NRZ
• Symbols independent and equally likely to be 0 or A
1
P (b[n] = 0) = P (b[n] = A) =
2
35 / 45
Unipolar NRZ
∞
A2 T A2 T X
Su (f ) = sinc2 (fT ) + sinc2 (fT ) e −j2πkfT
4 4
k =−∞
∞
A2 T A2 X n
= sinc2 (fT ) + sinc2 (fT ) δ f−
4 4 n=−∞
T
A2 T A2
= sinc2 (fT ) + δ(f )
4 4
36 / 45
Normalized PSD plot
1
Unipolar NRZ
Su (f )
0.5
A2 T
0
0.5 1 1.5 2
fT
37 / 45
Polar NRZ
• Symbols independent and equally likely to be −A or A
1
P (b[n] = −A) = P (b[n] = A) =
2
Su (f ) = A2 T sinc2 (fT )
38 / 45
Normalized PSD plots
1
Unipolar NRZ
Polar NRZ
Su (f )
0.5
A2 T
0
0.5 1 1.5 2
fT
39 / 45
Manchester
• Symbols independent and equally likely to be −A or A
1
P (b[n] = −A) = P (b[n] = A) =
2
• P(f ) = jT sinc fT
2 sin πfT
2
• Power Spectral Density
2 2 fT 2 πfT
Su (f ) = A T sinc sin
2 2
40 / 45
Normalized PSD plots
1
Unipolar NRZ
Polar NRZ
Manchester
Su (f )
0.5
A2 T
0
0.5 1 1.5 2
fT
41 / 45
Bipolar NRZ
• Successive 1’s have alternating polarity
0 → Zero amplitude
1 → +A or − A
1
P (b[n] = 0) =
2
1
P (b[n] = −A) =
4
1
P (b[n] = A) =
4
A2 /2
k =0
Rb [k ] = − A2 /4 k = ±1
0 otherwise
A2 A2 j2πfT
2 −j2πfT
Su (f ) = T sinc (fT ) − e +e
2 4
A2 T
= sinc2 (fT ) [1 − cos(2πfT )]
2
= A2 T sinc2 (fT ) sin2 (πfT )
43 / 45
Normalized PSD plots
1
Unipolar NRZ
Polar NRZ
Manchester
Bipolar NRZ
Su (f )
0.5
A2 T
0
0.5 1 1.5 2
fT
44 / 45
Thanks for your attention
45 / 45